(3NHGjG GdRhGjG ajeG aj GdQLGd ef GdHbGjGs - (3CMeO Hf eMeO Hf YeQ, TgGH GdOjf GdNaGLj GdeUQj , GdTgGH GdNaGLj,J (B1069 (3g` s
(3BNQgG (B:s
(3gPG BNQ eG JjSQ JMQjQg ef fSNI GdCUd hbO Hbj ajgG HYV JQGLe de jJjSQ fbdgG hVegG dCNhGJgG dVjb GdhbJ hbO CdMb GdeDda HYV JQGLe GdCaGVd GdMdHjjf s
(3GfXQ HQbe (B224s
(3HQbe (B1034 (3JGQjNs
(3fSNI SGOSIs
(3hHYOgG JQLeI hGajI ddNaGLj MhJ GdcKjQ ef TYQg hJbY gPg GdJQLeI ai (B25 (3hQbI s
(3jfbU ef Ghdg SWhQkG ef GdoebOeI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs